Thermal Manikin Evaluation of Gender Sweat Differences While Wearing a Ballistic Vest. (April 2016) - Domina, Tanya; An, Su Kyoung; Kinnicutt, Patrick George
The purpose of this research was to determine if gender-related thermoregulatory differences impacted relative humidity levels in the microclimate while wearing a unisex ballistic vest. Data was collected using a sweating thermal manikin customized to simulate high-intensity sweat rates. Sensors were used to collect microclimate data between the uniform layers. The male and female thermal manikin exhibited no significant differences in microclimate data in the layers of the back of the uniform while wearing the ballistic vest. There was a significant statistical difference between the male and female manikin for the frontal region with women exhibiting lower RH values. Without the ballistic vest, the female manikin exhibited significantly lower RH values in the microclimate region, both front and back. There were no significant differences in RH values for the male thermal manikin with versus without the ballistic vest.